2014
DOI: 10.1111/age.12173
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in nine native Turkish sheep breeds based on microsatellite analysis

Abstract: The genetic variability of 204 sheep from nine breeds (Awassi, Çine Çaparı, Karakaş, Karya, Karayaka, Morkaraman, Norduz, Sakız and Tuj) growing in four different regions (western, northern, eastern and south-eastern Anatolia) was assessed using 18 microsatellite loci. High mean number of alleles, allelic richness and factorial correspondence analysis showed the degree of admixture between native sheep breeds of Turkey. The Karya and Çine Çaparı breeds were observed as the most distinct of the breeds, and poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
24
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 21 publications
11
24
7
Order By: Relevance
“…Obtained molecular genetic parameters (Na, Ne, PIC and Hª) obtained from this study were higher than previous research (Farid et al 2000;Arranz et al 2001;Santos-Silva et al 2008;Jyotsana et al 2010;Al-Barzinji et al 2011;Hoda & Marsan 2012;Gaouar et al 2014Gaouar et al , 2015bGaouar et al , 2016aGaouar et al , 2016bYilmaz et al 2014;Kdidi et al 2015;Othman et al 2016). These results indicated that microsatellites used in the present study have a high confidence to reveal genetic diversity for these breeds.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Obtained molecular genetic parameters (Na, Ne, PIC and Hª) obtained from this study were higher than previous research (Farid et al 2000;Arranz et al 2001;Santos-Silva et al 2008;Jyotsana et al 2010;Al-Barzinji et al 2011;Hoda & Marsan 2012;Gaouar et al 2014Gaouar et al , 2015bGaouar et al , 2016aGaouar et al , 2016bYilmaz et al 2014;Kdidi et al 2015;Othman et al 2016). These results indicated that microsatellites used in the present study have a high confidence to reveal genetic diversity for these breeds.…”
Section: Discussioncontrasting
confidence: 73%
“…It can be said that there is loss of heterozygosity in four microsatellite loci studied considering F IS value is also known as the inbreeding coefficient. It is noteworthy that obtained general mean of F ST value is higher than earlier studies (Cemal et al 2013;Ben Sassi-Zaidy et al 2014;Ocampo et al 2016) and lower than others (Sodhi et al 2006;Yilmaz et al 2014). The differences between the previous literature and the present study were mainly due to non-comparative aspects such as studied microsatellite and breed differences.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In particular, the Food and Agriculture Organization, FAO (2011) recommend the use of microsatellite systems to identify diversity in domestic animals, and a large number of studies have been performed in multiple species including chickens (Tadano et al, 2014;Abebe et al, 2015), cattle (Pelayo et al, 2015;Sharma et al, 2015), pigs (Choi et al, 2014;Revidatti et al, 2014), sheep (Agaviezor et al, 2012;Yilmaz et al, 2014;Ćurković et al, 2016), and goats (Nomura et al, 2012;Wei et al, 2014). Most previous studies have shown that the breeds cluster according to their geographic location, and vary in the degree of diversity depending on the breeding and management histories of the breeds using these types of marker systems, which were typically co-dominant and assumed to be drifting (Granevitze et al, 2009).…”
Section: Introductionmentioning
confidence: 99%